Značilnosti in različni izidi zdravstvene socializacije v mladostništvu - Marčič, Renata (Farmacevtski vestnik, 2009)
Adolescence is a period of many changes in one's life on psysical level as well as on psychological and social level. Every adolescent more or less successfully encounters basic developmental tasks; the characteristic and outcomes of dealing with these tasks reflect themselves on his future life. One of important areas of adolescent's life is health socialization that can be seen through his attitude towards health, medicaments, health workers, health system, and through health related behavior, namely health risk behavior as well as health enhancing behavior. The article outlines the characteristics of adolescent's psychosocial development and health related behavior, and calls attention to the health risk and protection factors. Furthermore it indicates some guidelines for effective cooperation of pharmacists in health socialization of adolescents.
Keywords: mladostniki; vedenje; zdravje